2015
DOI: 10.4314/ajtcam.v12i5.18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of topical antimicrobial ointment formulations of essential oil of <i>Lippia multiflora</i> moldenke

Abstract: Background: Essential oil of Lippia multiflora (lippia oil) has been reported to possess antibacterial and antifungal activities. This study was aimed at developing an effective topical formulation of the oil for the treatment of skin infections. Materials and Methods: Lippia oil was extracted from leaves of L. multiflora by hydrodistillation. Different concentrations of the oil were incorporated into six different ointment bases. Tween 80 was incorporated at different concentrations into ointments containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The findings of this study revealed that the most effective inhibitory action was obtained when lippia oil (10% w/w ) was combined with Hydrous Wool Fat Ointment BP (British Pharmacopoeia method) or Simple Ointment BP, with added Tween 80 (6% w/w ) upon testing of C. pseudotropicalis and C. albicans . The incorporation of Tween 80 further enhanced the efficacy of this formulation, suggesting its suitability as a nonconventional treatment strategy [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study revealed that the most effective inhibitory action was obtained when lippia oil (10% w/w ) was combined with Hydrous Wool Fat Ointment BP (British Pharmacopoeia method) or Simple Ointment BP, with added Tween 80 (6% w/w ) upon testing of C. pseudotropicalis and C. albicans . The incorporation of Tween 80 further enhanced the efficacy of this formulation, suggesting its suitability as a nonconventional treatment strategy [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ten milliliters of sterile normal saline containing 3% w/v Tween 80 will be used to disperse the spores with the aid of sterilized glass beads (Oladimeji, et al, 2015). Standardization of the spore suspension to 1.0×10 6 spores/mL will be achieved with a UV spectrophotometer (Spectronic 20D; Milton Roy Company, Pacisa, Madrid, Spain) at 530nm (OD at 530) of the suspensions and adjusted to a transmittance of 70-72%.…”
Section: Fungal Preparationmentioning
confidence: 99%
“…Spreadability as shown in Fig. 8 is a parameter which denotes the ability, ease of application and extent an ointment would spread on the skin after application (Oladimeji et al, 2015). All formulations had satisfactory spreadability.…”
Section: Spreadability Of Formulationsmentioning
confidence: 99%